Few vertebrate species dominate the Borrelia burgdorferi s.l. life cycle - Hofmeester, T R; Coipan, E C; van Wieren, S E; Prins, H H T; Takken, W; Sprong, H (Environmental research letters, 2016)
Background. In the northern hemisphere, ticks of the Ixodidae family are vectors of diseases such as Lyme borreliosis, Rocky Mountain spotted fever and tick-borne encephalitis. Most of these ticks are generalists and have a three-host life cycle for which they are dependent on three different hosts for their blood meal. Finding out which host species contribute most in maintaining ticks and the pathogens they transmit, is imperative in understanding the drivers behind the dynamics of a disease. Methods. We performed a systematic review to identify the most important vertebrate host species for Ixodes ricinus and Borrelia burgdorferi s.l. as a well-studied model system for tick-borne diseases. We analyzed data from 66 publications and quantified the relative contribution for 15 host species. Review results. We found a positive correlation between host body mass and tick burdens for the different stages of I. ricinus. We show that nymphal burdens of host species are positively correlated with infection prevalence with B. burgdorferi s.l., which is again positively correlated with the realized reservoir competence of a host species for B. burgdorferi s.l. Our quantification method suggests that only a few host species, which are amongst the most widespread species in the environment (rodents, thrushes and deer), feed the majority of I. ricinus individuals and that rodents infect the majority of I. ricinus larvae with B. burgdorferi s.l. Discussion. We argue that small mammal-transmitted Borrelia spp. are maintained due to the high density of their reservoir hosts, while bird-transmitted Borrelia spp. are maintained due to the high infection prevalence of their reservoir hosts. Our findings suggest that Ixodes ricinus and Borrelia burgdorferi s.l. populations are maintained by a few widespread host species. The increase in distribution and abundance of these species, could be the cause for the increase in Lyme borreliosis incidence in Europe in recent decades.